2017
DOI: 10.3389/fnmol.2017.00226
|View full text |Cite
|
Sign up to set email alerts
|

SDF1-CXCR4 Signaling Maintains Central Post-Stroke Pain through Mediation of Glial-Neuronal Interactions

Abstract: Central post-stroke pain (CPSP) is an intractable central neuropathic pain that has been poorly studied mechanistically. Here we showed that stromal cell-derived factor 1 (SDF1 or CXCL12), a member of the CXC chemokine family, and its receptor CXCR4 played a key role in the development and maintenance of thalamic hemorrhagic CPSP through hypoxia inducible factor 1α (HIF-1α) mediated microglial-astrocytic-neuronal interactions. First, both intra-thalamic collagenase (ITC) and SDF1 injections could induce CPSP t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 64 publications
4
25
0
Order By: Relevance
“…Accumulating evidence indicated that immunemodulators play a key role in regulating synaptic plasticity and neuronal excitability, contributing to the persistence of various pain intensities (Jiang et al, 2017;Yang et al, 2017;Wu et al, 2019). The role of CXCL1, a member of the CXC family, depends on its primary receptor CXCR2 (Carreira et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicated that immunemodulators play a key role in regulating synaptic plasticity and neuronal excitability, contributing to the persistence of various pain intensities (Jiang et al, 2017;Yang et al, 2017;Wu et al, 2019). The role of CXCL1, a member of the CXC family, depends on its primary receptor CXCR2 (Carreira et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Considerable research has suggested that numerous extracellular signaling molecules and intracellular transduction pathways are involved in chronic pain. 21 24 The Janus family tyrosine kinase (JAK)/signal transducers and activators of transcription (STAT) pathway is one of the most important cell signaling pathways in chronic pain, which includes four types of JAK and seven types of STAT. 25 , 26 Our previous study has demonstrated that STAT1 contributes to CIBP by regulating MHC II expression in spinal microglia.…”
Section: Introductionmentioning
confidence: 99%
“…We speculated that the protracted analgesic effect was largely because of the plerixafor not only reduced the expression of Nav1.8 and Nav1.9, but also has the ability to relieve in ammation in compressed DRG which was also a pivotal mechanism for neuronal hyperexcitability and chronic pain. In supporting, recent studies have demonstrated that the pro-in ammatory cytokines dramatically up-regulated accompanying with several anti-in ammatory cytokines down-regulated in compressed DRG [22], while plerixafor has been proven to be able to reducing the expression of TNF-α, IL-1β, IL-6 and in ammatory cell in ltration in the nervous system [10,35]. Collectively, the above characteristics and advantages of plerixafor make it an effective and applicable therapeutic medicine for neuropathic pain.…”
Section: Blocking Cxcr4 With Plerixafor Is a Potential And E Cient Trmentioning
confidence: 93%
“…In chronic constriction injury (CCI) and SNI model, elevation of CXCR4 immunoreactivity has also been demonstrated in the DRG neuronal soma [36,37]. The expression level of CXCR4 in the CNS could also be obviously enhanced under central neuropathic pain situations such as central post stroke pain [10], spinal cord ischemia-reperfusion [38], spinal cord contusion injury [39]. This inducible expression pattern of CXCR4 enable CXCR4 as an ideal analgesic target.…”
Section: Blocking Cxcr4 With Plerixafor Is a Potential And E Cient Trmentioning
confidence: 98%
See 1 more Smart Citation